Mediation of Illness and Disability: The Complexity of Articuliation - Šmitienė, Giedrė; Jonutytė, Jurga (Colloquia, 2021)
The article looks into Jonas Mačiukevičius’s autobiographical novella Laikrodžiai nesustoja [Clocks Don’t Stop Running, 1968], which delves into a young person’s decade-long experience of a serious illness. The analysis of the story branches out from the research of the authors of the article about the concept of disability in life stories. The authors have also written about the reception of this work in the 1960s. This time, the article discusses the literary features of the text itself and the depiction of the experience of a sick and disabled body.The authors of the article phenomenologically analyze the multilayered nature of the experience of the illness in the text: they analyze the writer’s choice to tell the story from the patient’s perspective and draw attention to the relationship with one’s impaired body and the dynamics of the patient’s self-perception. Analyzing deeper, the authors show that corporeality and dignity are inextricably linked. The experience of pain reveals that pain is never purely physical (it is always existential) and that it is mediated. The experience of illness, like that of disability, depends on the attitudes of the people around us, on their thematized and latent attitudes, which lend different meanings to human vulnerability. According to the authors, Mačiukevičius’s work, which spoke of vulnerability of a body during the Soviet era, could be read afresh today, when ableism has been increasingly appearing in the humanities and social sciences.
Keywords: one’s own body; illness; disability; pain; vulnerability; Jonas Mačiukevičius; phenomenology